Evidence for the Influence of DE3 Tide on the Occurrence of Equatorial Counterelectrojet - Singh, Dupinder; Gurubaran, S.; He, Maosheng (My University, 2018)
The long-term Challenging Minisatellite Payload magnetometer data are analyzed to derive the equatorial counterelectrojet (CEJ) signatures globally over a range of local times. The resultant local time-longitude map of CEJ occurrence rate shows a strong influence of the diurnal eastward propagating wave number 3 (DE3) nonmigrating tide during July–September months. DE3 is also shown to account for the reduction of CEJ occurrence at certain longitudes. These aspects of DE3 tide-CEJ relationship have implications for understanding the seasonal and longitudinal variations of CEJ. Observations of zonal winds from the Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) Doppler Interferometer instrument on board the TIMED satellite are used to establish these findings.
Keywords: Atmospheric tides; Equatorial Counterelectrojet; Counterelectrojet; CEJ